A new species of the bee genus Chlerogella from Panama (Hymenoptera: Halictidae) - Engel, Michael S. (Zootaxa, 2003)
A new species of the Neotropical bee genus Chlerogella Michener, 1954 (Halictinae: Augochlorini) is described and figured from San Blas, Panama. Chlerogella clidemiae sp. nov., is differentiated from other members of its genus and is the first species with a floral record; captured on flowers of Clidemia crenulata Gleason (Melastomataceae).